2016
DOI: 10.1038/srep24395
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of Indian heatwaves

Abstract: India suffers from major heatwaves during March-June. The rising trend of number of intense heatwaves in recent decades has been vaguely attributed to global warming. Since the heat waves have a serious effect on human mortality, root causes of these heatwaves need to be clarified. Based on the observed patterns and statistical analyses of the maximum temperature variability, we identified two types of heatwaves. The first-type of heatwave over the north-central India is found to be associated with blocking ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
171
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(180 citation statements)
references
References 22 publications
9
171
0
Order By: Relevance
“…Furthermore, Jenamani [] observed that the recurving of cyclonic storms strengthen low‐level westerly and thus prevent the onset of cooler sea breeze over coastal region, causing persistent heat waves. In contrast, the northcentral India heat waves are due to the anomalous quasi‐stationary wave originating at the entrance of the African Jet [ Ratnam et al ., ].…”
Section: Concurrence Of Droughts and Heat Wavesmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, Jenamani [] observed that the recurving of cyclonic storms strengthen low‐level westerly and thus prevent the onset of cooler sea breeze over coastal region, causing persistent heat waves. In contrast, the northcentral India heat waves are due to the anomalous quasi‐stationary wave originating at the entrance of the African Jet [ Ratnam et al ., ].…”
Section: Concurrence Of Droughts and Heat Wavesmentioning
confidence: 97%
“…Moreover, the large‐scale climatic mode that modulate of the mean and extreme metrics of temperatures is the rising SST over Indian Ocean (SST‐IO) (heat waves generally occur during or succeeding El Niño events), which also induces less rainfall in India [ Panda et al ., ; Roxy et al ., ; Ratnam et al ., ; Rohini et al ., ]. Therefore, it is difficult to separate the influence of the significantly warming SST‐IO during 1951–2013 and 1981–2013 from that of the corresponding drying tendency (Figures d and f).…”
Section: Concurrence Of Droughts and Heat Wavesmentioning
confidence: 99%
“…Hospitals were overwhelmed with patients suffering from heat-related symptoms and at some point had to turn away patients (Salim et al 2015). It is difficult to be precise about the ultimate number of fatalities associated with these heat waves, but upwards of 2500 excess deaths are estimated to have occurred in the Indian heat wave (Ratnam et al 2016) and at least 700 alone in the Pakistani megacity of Karachi (Masood et al 2015) with many more throughout the country.…”
Section: Table Of Contentsmentioning
confidence: 99%
“…The methodology followed for identifying the cold wave events is similar to that used by the authors for identifying heat wave events over India15. In this study, for identifying the cold wave events, we use the high resolution gridded temperature daily minimum temperature dataset of the India Meteorological Department (IMD)16.…”
Section: Methodsmentioning
confidence: 99%